Perbandingan Latihan Push Up dan Beban Dumbell Terhadap Kecepatan Pukulan Straight pada Atlit Tinju Amatir Sasana Lipang Bajeng Kabupaten Takalar - Latuheru, Melerand Evert; Lolangluan, Welem Arawaman; Wattimury, Hermanus (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2021)
This study aims to find out about the comparison of push up training and dumbbell weights to the speed of a straight punch in amateur boxing athletes. This type of quantitative research is an experimental form using a cross sectional study approach. The population is all 30 boxing amateur boxing athletes. The sampling technique is by sampling saturation. The population was used as a sample of Research Instruments divided into 2 groups of 15 people. The technique of group division technique uses the Randomized group method, while using the T-test. The results showed that there was no comparison as well as a significant difference between push-up training with dumbbell load to 0.454 straight stroke speed, seen from the t-count of push-up and dumbbell load -0,770